Prevalence of Hepatitis B Surface Antigen (HBsAg) Among HIV Seropositive Patients - Anamika Vyas; Ramavtar Saini; Pooja Gangrade (Journal of Basic & Applied Sciences, 2012)
Introduction: Human Immunodeficiency Virus (HIV) and Hepatitis B virus (HBV) share the routes of transmission as a consequences infection with Hepatitis B Virus are expected to occur in HIV infected patients. The co-infection of Hepatitis B Virus (HBV) with the Human Immunodeficiency Virus (HIV) have become a major health care catastrophe as it complicates the clinical course, management and therapy for HIV infection. Hence it is important to identify them as early as possible. Aim: The prevalence of HBV co-infection with HIV varies widely across different studies within India and outsides. This study is planned to evaluate the prevalence of HIV-HBV co-infection by HBsAg screening in HIV seropositive patients in our region. Material and Method: A total of 140 HIV seropositive patients were screened for the presence of Hepatitis B virus on the basis of the presence of HBsAg. Result: In patients infected with HIV the prevalence of HBsAg was 7.1% (10/140) wherease in control group it was 1% (5/500). Discussion: Our study documents fairly high rate of Hepatitis B co-infection among HIV seropositive patients suggesting that it should be mandatory to screen every HIV seropositive patient and their sexual partners for co infection with HBV and vice versa for early detection and a simultaneous treatment of hepatitis B co-infection beside HIV infection management to reduce the morbidity, delay mortality and improve quality of life in HIV-AIDS patients.